Haemophilus ducreyi DNA is detectable on the skin of asymptomatic children, flies and fomites in villages of Papua New Guinea. - Wendy Houinei; Charmie Godornes; August Kapa; Sascha Knauf; Eric Q Mooring; Camila González-Beiras; Ronald Watup; Raymond Paru; Paul Advent; Sivauk Bieb; Sergi Sanz; Quique Bassat; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Haemophilus ducreyi and Treponema pallidum subsp. pertenue are major causes of leg ulcers in children in Africa and the Pacific Region. We investigated the presence of DNA (PCR positivity) from these bacteria on asymptomatic people, flies, and household linens in an endemic setting. METHODOLOGY/PRINCIPAL FINDINGS:We performed a cross-sectional study in rural villages of Lihir Island, Papua New Guinea during a yaws elimination campaign. Participants were asymptomatic subjects recruited from households with cases of leg ulcers, and from households without cases of leg ulcers. We rubbed swabs on the intact skin of the leg of asymptomatic individuals, and collected flies and swabs of environmental surfaces. All specimens were tested by PCR for H. ducreyi and T. p. pertenue DNA. Of 78 asymptomatic participants that had an adequate specimen for DNA detection, H. ducreyi-PCR positivity was identified in 16 (21%) and T. p. pertenue-PCR positivity in 1 (1%). In subgroup analyses, H. ducreyi-PCR positivity did not differ in participants exposed or not exposed to a case of H. ducreyi ulcer in the household (24% vs 18%; p = 0.76). Of 17 cultures obtained from asymptomatic participants, 2 (12%) yielded a definitive diagnosis of H. ducreyi, proving skin colonization. Of 10 flies tested, 9 (90%) had H. ducreyi DNA and 5 (50%) had T. p. pertenue DNA. Of 6 bed sheets sampled, 2 (33%) had H. ducreyi DNA and 1 (17%) had T. p. pertenue DNA. CONCLUSIONS/SIGNIFICANCE:This is the first time that H. ducreyi DNA and colonization has been demonstrated on the skin of asymptomatic children and that H. ducreyi DNA and T. p. pertenue DNA has been identified in flies and on fomites. The ubiquity of H. ducreyi in the environment is a contributing factor to the spread of the organism.